A new name, synonyms, and typifications in Eugenia (Myrtaceae) from São Paulo, Brazil - Valdemarin, Karinne Sampaio; Faria, Jair Eustáquio Quintino De; Sobral, Marcos; Bünger, Mariana; Mazine, Fiorella F. (Phytotaxa, 2020)
Eugenia is an important genus of Brazilian Myrtaceae due to its representativity, ecological and economic aspects. During a study on the taxonomy of Eugenia for the “Flora Fanerogâmica do Estado de São Paulo” project, some names in need of nomenclatural and taxonomic changes were identified. A new name, and six new synonyms are herein presented, as well as the designation of ten lectotypes, two epitypes, one neotype, and the elucidation of a not validly published name, including a discussion of each case.